2019
DOI: 10.33258/biarjohs.v1i1.18
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Buy and Sell Financing (Murabahah), Profit Share Financing (Mudarabah), Equity Capital Financing (Musyarakah) and Non-Performing Financing Ratio on Profitability Level of Sharia Commercial Banks in North Sumatera

Abstract: The aim of this study is to determine the effect of buy and sell financing (murabahah), profit share financing (mudarabah), equity capital financing (musyarakah) and non-performing financing (NPF) ratio  as a whole (Simultaneous) on profitability level of Sharia Commercial Banks in North Sumatera. The population of the study are all Sharia Commercial Banks in North Sumatera which amounted to 6 banks. The population in this study is the annual financial reports regarding Islamic banking which taken from the fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
2
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 0 publications
2
12
2
10
Order By: Relevance
“…Likewise, the profits gained by the Sharia Banks are low, so the financing for the proceeds distributed by the Sharia Banks will be decreased. The statement is in accordance with Yusuf et al [2] and Usanti and Shomad [3] that Return on Assets (ROA) was positively influential in the financing of the proceeds.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…Likewise, the profits gained by the Sharia Banks are low, so the financing for the proceeds distributed by the Sharia Banks will be decreased. The statement is in accordance with Yusuf et al [2] and Usanti and Shomad [3] that Return on Assets (ROA) was positively influential in the financing of the proceeds.…”
Section: Introductionsupporting
confidence: 87%
“…Previous research that examines the financing for the outcome, a study that examines mudharabah deposits on sharia banks is conducted in Indonesia [1]. In addition, earlier research also analyzed the influence of Buy and Sell Financing (Murabahah), Profit Share Financing (Mudarabah), Equity Capital Financing (Musyarakah) and Non-Performing Financing Ratio on Profitability pad Bank Sharia in North Sumatera [2]. The Reconstruction of Financing Based on the Principle of Profit and Loss in Sharia Banking agreement has been examined in depth [3].…”
Section: Introductionmentioning
confidence: 99%
“…The significance value of 0,000 is less than 0,05. Thus, it can be concluded that there is an effect of sharing financing and qardh financing simultaneously (Yusuf et al, 2019).…”
Section: Simultaneously Testmentioning
confidence: 95%
“…Profitability (profit) is the result of the wisdom taken by management. Profit ratio to measure how much the level of profit that can be obtained by the company (Yusuf et al, 2019). Profitability shows the level of profitability of a well-managed company, the higher the profitability, the value.…”
mentioning
confidence: 99%